Regional Variation in Age at First Marriage Among Women of Reproductive Age in Nigeria (Journal of Science and Technology, 2023)
The society and the environment have great influence on the attitudes and the decisions made by her residents. The age at which a woman enters marriage to some extent is influenced by the society and the environment she lives in and some other socio-demographic factors. This study employs a hierarchical survival analysis which account for state differences in the age at first marriage among Nigerian women using the dataset from 2018 National Demographic Health survey. The Cox model with two independent random effects was used to provide parameter estimates as well as estimates of the random effects variances at all the levels. It was found that state heterogeneity had the highest contribution and location of residence within the state also contributed to the differences in the timing of marriage. The study also revealed that region, location of residence, wealth index, respondent age at first sex, birth cohort, religious affiliation and educational qualification of the women were significant factors in determining the age at first marriage.